Provider perceptions on HIV risk and prevention services within permanent supportive housing. Issue 10 (3rd October 2017) - Wenzel, Suzanne L.; Henwood, Benjamin; Harris, Taylor; Winetrobe, Hailey; Rhoades, Harmony
ABSTRACT: Permanent supportive housing (PSH) is an evidence-based solution to homelessness for persons experiencing chronic or long-term homelessness and one or more physical or behavioral health problems. Health services through PSH typically focus on physical and behavioral health. With the exception of programs specifically designed for persons living with HIV/AIDS, little attention has focused on services through PSH to prevent transmission of HIV or other sexually transmitted infections (STIs), yet sexual risk behavior continues after homeless persons move into PSH. The purpose of this study was to investigate how PSH providers approach HIV prevention and the challenges they perceive surrounding HIV prevention in PSH. Results serve as a critical first step toward addressing the acceptability and feasibility of providing HIV/STI prevention services to PSH residents. As part of a longitudinal mixed methods study examining HIV risk and prevention behavior among homeless unaccompanied adults moving into PSH in Los Angeles, we conducted eleven focus groups with a total of 60 frontline staff across 10 PSH agencies. Thirty-three percent of focus group participants were African American, 32% were Hispanic, and 55% were women. Results suggest that provider awareness and knowledge of PrEP is very limited, and provision of formal HIV prevention programing for residents is perceived as challenging. Informal, ad hoc conversations with residents about sexual risk and HIV prevention do occur when providers have rapport with clients and perceive risk. There are significant gaps in HIV prevention services through PSH but also opportunities to enhance providers' efforts to promote the health of residents through prevention.